NUMBED BY PLEASURE: THE DISAPPEARANCE OF DEEP LIVING IN BRAVE NEW WORLD AND MODERN WORLD - Dahiya, Yash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Aldous Huxley’s Brave New World (1932) has been so widely accepted and studied that the title has gained popularity as a metaphor in scholarly discourse. This novel depicts a dystopian future in which the global government controls people’s lives, employment, and leisure activities. We are shown a striking image of people living in harmony and comfort, but the reason for this is that they have sacrificed their uniqueness, autonomy, and emotional complexity. Artificial means are used to keep people happy and pleased all the time in this world, so they don’t question anything that happens in their lives. Affecting people’s lives with manufactured joy, capitalists keep them from thinking critically and logically. The novel reflects how the relationships, emotions, and experiences of people are shallow and fake. In this paper, two worlds are compared. One is the real world we live in, and the other is the one that Huxley created. The world we are living in today is not controlled by the government, but there are many ways through which our lives are somehow shaped and controlled by digital media, consumer culture, and entertainment. The individuals of the present day, like the characters in Brave New World, also avoid uncomfortable emotions and critical thinking. This paper argues that when society’s primary goal is to be comfortable and content, it somehow eliminates the essential elements that give life greater meaning, such as creativity, hardship, introspection, and love. In conclusion, this essay argues that while technological progress and entertainment are important parts of our lives, they shouldn’t take the place of the values that people have given us.